MICROPROPAGATION OF BLACKBARRY CV. BRAZOS - AUGUSTO, Carolina Smanhoto Schuchovski (Scientia Agraria, 2002)
Blackberry (Rubus sp.) is a species vegetatively propagated, specially by root and herbaceous cuttings. However, there are many phytosanitary problems derived from these propagation methods. The aim of this work was to achieve an efficient blackberry micropropagation protocol, offering an alternative to the tradicional propagation methods used in Brazil. Mother plants from Brazos cultivar were kept into a greenhouse. Disinfestation experiments with nodal stems were done to test the imersion in a 0,5% solution of sodium hypochlorite for 0, 10, 20 and 30 minutes. In the establishment stage, several concentrations of the antioxidant PVP K 25 (0, 1 and 2 g.L-1) were tested in the meristem culture. In the multiplication stage, different cytokinins (BAP, kinetin, zeatin, 2iP and thidiazuron) were tested in two concentrations (5 and 10 mM) plus growth regulator free medium. This experiment was repeated for more three subcultures. Another experiment during the multiplication stage was done to test different culture media with the treatments as follows: MS, MS/2, AND, QL and WPM. This experiment was repeated for more two subcultures. In the following stage, an in vitro rooting experiment was done with or without imersion in a 1 mM solution of indolbutiric acid. Another rooting experiment was done in a greenhouse with intermittent mist with the plants proceeding from the same treatments from the multiplication experiment with different cytokinins. In the final stage the influence of sucrose from the rooting media was tested in the acclimatization in greenhouse under plastic tunel or under intermittent mist. The results found were that the explant contamination was reduced with the use of NaOCl in all the imersion time. The PVP, in the two tested concentrations, reduced oxidation. In the multiplication experiment with cytokinins, thidiazuron was not viable because of the shoot malformation and great callus formation. The highest multiplication rates were obtained with BAP in the two tested concentrations, obtaining 4.4, 6.1, 7.9 and 2.6 shoots per explant in the 5 mM concentration and 4.3, 4.7, 4.8 and 2.1 shoots per explant in the 10 mM concentration, in the four subcultures. In the multiplication experiment with culture media, in the three subcultures, there was a tendency of higher multiplication in MS media, reaching 3.9, 4.3 and 2.5 shoots per explant in the first, second and third subculture. The percentage of rooting was higher than 95% in both treatments of in vitro rooting. For the ex vitro rooting experiment, the rooting and survival rates were 100%. In the acclimatization experiment all the treatments showed 100% of survival. It can be concluded that an efficient protocol for blackberry micropropagation is: disinfestation for 10 minutes imersion in sodium hypochlorite (0.5%), adding 1 g.L-1 of PVP in the initial stage, multiplication in MS media suplemented with BAP (5 mM) and in vitro rooting without indolbutiric acid and without sucrose in the culture media with acclimatization under plastic tunel or ex vitro rooting and acclimatization under intermittent mist in a greenhouse.